EFFECTS OF WALNUT LEAF EXTRACTS PREPARED IN DIFFERENT SOLVENTS ON SEED GERMINATION AND SEEDLING GROWTH OF WHEAT - Kilic, B.; Kocacaliskan, I.; Terzi, I. (SCIBULCOM LTD, 2014)
In this study, effects of walnut leaf extracts prepared in six different solvents, i. e. water, ethanol, methanol, aseton, tetrahydrofuran (THF) and dimethyl sulphoxide (DMSO), on seed germination and post-germinative seedling growth of wheat (Triticum vulgare L. cv Altay) have been investigated. Among the treatments, DMSO extract was only seen to inhibit germination percentage of the seeds at second day. It also decreased germination rate of the seeds significantly with respect to control. Root elongation was inhibited significantly by DMSO and water extracts, whereas, shoot elongation was inhibited by the treatments of DMSO, water, THF and methanol extracts in range of effectiveness grade from high to low. Root and shoot fresh weights were decreased by all the treatments. However, the highest inhibitory effect was generally found to be DMSO extract both in seed germination and seedling growth parameters. Thus, it was discussed in the manuscript that DMSO may be more efficient and proper solvent in extraction of walnut leaf.
Keywords: seed germination; seedling growth; solvents; walnut leaf extracts; JUGLANS-MANDSHURICA-MAXIM; JUGLONE; APOPTOSIS; Environmental Sciences & Ecology